2009
DOI: 10.1086/594124
|View full text |Cite
|
Sign up to set email alerts
|

Guillain‐Barré Syndrome and Influenza Virus Infection

Abstract: Influenza viruses are infrequent triggering agents of GBS but may play a significant role during major influenza outbreaks. Influenza-related GBS displays specific features and is not associated with antiganglioside antibody response, which suggests the presence of underlying immune mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 35 publications
4
82
1
4
Order By: Relevance
“…In addition, data from the systems monitoring influenza A(H1N1) 2009 monovalent vaccines suggest that the increased risk for GBS is approximately one or two additional cases per 1 million persons vaccinated, which is similar to that observed in some years for seasonal IIV (350)(351)(352)(353)(354)(355)(356). Studies have also shown an increased risk for GBS following influenza infection, of higher magnitude than the risk observed following influenza vaccination (338,357).…”
Section: Guillain-barré Syndrome and Iivmentioning
confidence: 62%
“…In addition, data from the systems monitoring influenza A(H1N1) 2009 monovalent vaccines suggest that the increased risk for GBS is approximately one or two additional cases per 1 million persons vaccinated, which is similar to that observed in some years for seasonal IIV (350)(351)(352)(353)(354)(355)(356). Studies have also shown an increased risk for GBS following influenza infection, of higher magnitude than the risk observed following influenza vaccination (338,357).…”
Section: Guillain-barré Syndrome and Iivmentioning
confidence: 62%
“…Seasonal influenza A and B have been serologically associated with GBS [6,7]. However, this association has been very scarce and has not been reported with the AMAN variant.…”
Section: Discussionmentioning
confidence: 99%
“…The most common pathogen associated with GBS is Campylobacter jejuni [4]. In addition, GBS cases have been reported following cytomegalovirus [7], Epstein-Barr virus [8], Mycoplasma pneumoniae [9], Haemophilus influenza [10], influenza virus [11], Hepatitis E [12], Dengue [13], Chikungunya (CHIKV) [14] and Zika virus (ZIKV) infections [15], among others. Moreover, vaccination campaigns against influenza A (H1N1) [4] and rabies prophylactic vaccination [16] were associated with a small risk of GBS.…”
Section: Introductionmentioning
confidence: 99%